Ukraine foreign exchange policy implementation: principles of building state bodies system in sphere regulating currency relations - Demenko, Karyna Eduardivna (Global Prosperity, 2023)
The article is devoted to the study of the principles of constructing a system of state bodies in the field of currency regulation as principles of implementing the state's currency policy. In the process of research, the author came to the conclusion that principles are guiding and regulatory fundamental principles that form the basis of any scientific knowledge or activity. The essence of the principles of constructing a system of state bodies in the field of currency regulation lies in their use as guiding and regulatory ideas, based on which a system of state bodies in the field of currency relations should be built and their activities organized. The research conducted by the author, both scientific sources and the practice of functioning of state bodies in the field of currency regulation, made it possible to attribute the principles of constructing a system of state bodies in this field to the principle of systemic state governance and the principle of a single regulatory body for currency relations. The author argues that the implementation of the principle of systemic construction of a system of state bodies in the field of currency regulation should take into account all the existing elements of the country's currency system. In this regard, the creation of a system of state bodies should be carried out through their institutional formation and the crystallization of powers that will cover all elements of the currency system. The implementation of the principle of a single regulatory body for currency relations involves the creation of an authorized body that will exclusively carry out currency regulation in the country. At the same time, Ukraine currently implements a mixed model of a system of state bodies in the field of currency regulation.